Literature Review: Hubungan Dukungan Suami Dengan Perilaku Wanita terhadap Deteksi Dini Kanker Serviks Metode Inspeksi Visual Asam Asetat (IVA) - Fitriani Fitriani (Universitas Malahayati Lampung, 2022)
ABSTRACT: LITERATURE REVIEW: RELATIONSHIP OF HUSBAND SUPPORT WITH WOMEN'S BEHAVIOR TOWARDS EARLY DETECTION OF CERVIC CANCER METHOD OF VISUAL INSPECTION OF ACETIC ACID (IVA) Background : Cervical cancer is ranked as the fourth most commonly suffered by women with an estimated 570,000 new cases in 2018 representing 6.6% of all female cancers in the world and being the fourth highest mortality rate. Early detection of cervical cancer in women aged 30-50 in Indonesia in 2019 showed that 84,1859 IVA positive and 5015 suspected cervical cancer. Early detection program is mainly carried out in cervical and breast cancer which is the highest type of cancer in Indonesia. Screening cervical cancer with the Visual Inspection method of Acetic Acid (IVA) because this method is in accordance with conditions in developing countries including Indonesia, the technique is easy and the sensitivity level is high, fast and accurate enough to find abnormalities at the stage of cell abnormalities or before pre-cancer.Research objectives: To conduct a review on several literature related to the relationship of Husband Support With Female Behavior towards Early Detection of Cervical Cancer Acetic Acid Visual Inspection Method (IVA)Research Methods: Using the search method and review of the article